Ketogenesis nutritionally supports brain during bacterial infection in Drosophila - Krejčová, Gabriela; Novotná, Diana; Bajgar, Adam (Brain, behavior, and immunity, 2025)
Mounting an immune response is a nutritionally demanding process that requires the systemic redistribution of energy stores towards the immune system. This is facilitated by cytokine-induced insulin resistance, which simultaneously promotes the mobilization of lipids and carbohydrates while limiting their consumption in immune-unrelated processes, such as development, growth, and reproduction. However, this adaptation also restricts the availability of nutrients to vital organs, which must then be sustained by alternative fuels. Here, we employed an experimental model of severe bacterial infection in Drosophila melanogaster to investigate whether ketogenesis may represent a metabolic adaptation for overcoming periods of nutritional scarcity during the immune response. We found that the immune response to severe bacterial infection is accompained by increased ketogenesis in the fat body and macrophages, leading to elevated levels of β-hydroxybutyrate in circulation. Although this metabolic adaptation is essential for survival during infection, it is not required for the elimination of the pathogen itself. Instead, ketone bodies predominately serve as an energy source for the brain neurons during this period of nutrient scarcity.
Keywords: Animals; Ketone bodies; tukové těleso; Metabolism; Fat Body; makrofágy; Bacterial Infections; energetický metabolismus; Adipocytes; Macrophages; β-hydroxybutyrate; Energy Metabolism; neurony; mozek; Neurons; Ketone Bodies; Brain; Drosophila melanogaster; The fat body; 3-Hydroxybutyric Acid; zvířata; Infection; ketolátky; kyselina 3-hydroxymáselná; bakteriální infekce